2020
DOI: 10.1039/c9ja00415g
|View full text |Cite
|
Sign up to set email alerts
|

The accurate determination of number concentration of inorganic nanoparticles using spICP-MS with the dynamic mass flow approach

Abstract: Methodology for SI traceable determination of particle number concentration by reference NM-free spICP-MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 19 publications
(34 reference statements)
2
45
0
Order By: Relevance
“…6 Utilizing spICP-MS and the so-called dynamic mass flow (DMF) approach to calibrate the mass of the particle suspension transported into the plasma, the first quality control (QC) material, LGCQC5050, with an assigned nanoparticle number concentration value that is traceable to the SI unit for mass (kilogram) was released in 2019 by LGC. 12,23 Prior to the assignment of the number concentration value by LGC, this material was used as basis for the interlaboratory study reported here.…”
Section: Introductionmentioning
confidence: 99%
“…6 Utilizing spICP-MS and the so-called dynamic mass flow (DMF) approach to calibrate the mass of the particle suspension transported into the plasma, the first quality control (QC) material, LGCQC5050, with an assigned nanoparticle number concentration value that is traceable to the SI unit for mass (kilogram) was released in 2019 by LGC. 12,23 Prior to the assignment of the number concentration value by LGC, this material was used as basis for the interlaboratory study reported here.…”
Section: Introductionmentioning
confidence: 99%
“…Basic understanding of the accuracy of sp-ICP-MS measurement and data analysis approaches is hampered by a lack of NP reference materials certied for both element mass and number concentration. This lack of standards has led to inconsistent measurement practices among researchers, which may cause confusion for new practitioners of sp-ICP-MS. For example, there is little consensus on signicant measurement conditions such as optimal dwell time, most accurate method to determine transport efficiency and absolute elemental sensitivities, [55][56][57][58] or robust signal-thresholding criteria for NP identication. 59 There are, indeed, many researchers working to harmonize and standardize sp-ICP-MS measurements, [60][61][62][63] but, without a suite of well-characterized reference NPs, this process remains a challenge.…”
Section: Resultsmentioning
confidence: 99%
“…The method suggested by Cuello-Nunez and co-workers [26] was reproduced on two ICP-MS instrument platforms, a Perkin Elmer Nexion 300D and an Agilent 8900. The Perkin Elmer instrument was equipped with a Meinhard concentric nebuliser and a baffled non-refrigerated cyclonic spray chamber.…”
Section: Determination Of Transport Efficiency Based On the Dynamic M...mentioning
confidence: 99%
“…A possible explanation could be offered by the different configuration and temperatures of the two sample introduction systems. While the Perkin Elmer Nexion 300D was equipped with a non-cooled cyclonic chamber, the Agilent instrument was equipped with a cooled (2 • C) Scott-type spray chamber, very similar to the system used by Cuello and co-workers [26]. The DMF approach is an indirect method for the determination of the transport efficiency.…”
Section: Alternative Determination Of Transport Efficiency By the Dmf...mentioning
confidence: 99%